2011
DOI: 10.1038/ijo.2011.106
|View full text |Cite
|
Sign up to set email alerts
|

Parental perceptions of weight status in children: the Gateshead Millennium Study

Abstract: ObjectivesTo investigate parents’ perceptions of weight status in children and to explore parental understanding of and attitudes to childhood overweight.DesignQuestionnaires and focus groups within a longitudinal study.Subjects536 parents of Gateshead Millennium Study children, of which 27 attended 6 focus groups.Main outcome measuresParents’ perception of their child’s weight status according to actual weight status as defined by International Obesity Taskforce (IOTF) cut-offs. Focus group outcomes included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
85
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 21 publications
(39 reference statements)
8
85
0
2
Order By: Relevance
“…physical activity and healthy eating) rather than weight itself has been forwarded as one means of minimising stigma (15) , this is not without challenges; in the present study most parents considered that their child had a healthy diet and was already sufficiently active for health. While previous research suggests that parents' perceptions in this respect are often inaccurate (6,7) , they would be unlikely to be motivated towards change unless these perceptions changed too. One approach to tackling this may be for schools to engage parents and children in monitoring their diet and physical activity levels against recommended standards, in order to provide parents with more objective information with which to make more informed judgements.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…physical activity and healthy eating) rather than weight itself has been forwarded as one means of minimising stigma (15) , this is not without challenges; in the present study most parents considered that their child had a healthy diet and was already sufficiently active for health. While previous research suggests that parents' perceptions in this respect are often inaccurate (6,7) , they would be unlikely to be motivated towards change unless these perceptions changed too. One approach to tackling this may be for schools to engage parents and children in monitoring their diet and physical activity levels against recommended standards, in order to provide parents with more objective information with which to make more informed judgements.…”
Section: Discussionmentioning
confidence: 97%
“…An important initial step in the process of preventing and tackling childhood obesity is raising awareness among parents that their child is overweight (2,3) , as without parental involvement and support, the potential impact of interventions to reduce obesity is limited (4,5) . Past work suggests that fewer than half of parents of overweight children correctly recognise their child as such (6) , with some studies estimating this to be as low as 30 % (7) . An example of how parental awareness can be raised is provided by the UK National Child Measurement Programme (NCMP), a nationwide school-based monitoring programme introduced in the UK in 2006 (8) .…”
mentioning
confidence: 99%
“…6 A physician has to raise the topic of weight in the first place to record a weight and this conversation is initiated presumably mostly on visual perception. A substantial proportion of parents of obese children underestimate their child's weight status, 7,8 and healthcare professionals may be no more accurate than the general population at estimating children's and adults' weight status.…”
Section: Introductionmentioning
confidence: 99%
“…If a child is found to be overweight or obese, many school nurses notify the parent by sending a letter home with the child describing their placement on a BMI growth chart [35]. Since many parents do not favour 'official' methods of identifying overweight (i.e., BMI and/or percentiles), showed limited understanding of how overweight is defined for children, limited comprehension of the measures, and felt that they were irrelevant for their child [36,37], the letters from school nurses identifying weight status may not be effective. An evaluation of school based BMI and body composition screenings in California showed that only 12% of the letter formats contained an explanation of the measures used to determine the child's weight status [38] further limiting the parent's comprehension of the weight status conclusions.…”
Section: Journal Of Childhood Obesitymentioning
confidence: 99%